2011
DOI: 10.1097/nna.0b013e318221c260
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Nursing Characteristics on 30-Day Mortality

Abstract: Hospital nursing characteristics are an important consideration in efforts to reduce the risk of 30-day mortality of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 0 publications
7
83
0
Order By: Relevance
“…In a recent study, Aiken et al 1 link adequate nurse staffing and better-educated nurses in combination with a good work environment to decreased patient mortality, whereas hospitals with poor work environments were found to have the opposite outcome. In line with our study results, good nurse–physician relations and teamwork have been shown in a number of other studies to be positively related to patient safety outcomes 7 30…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, Aiken et al 1 link adequate nurse staffing and better-educated nurses in combination with a good work environment to decreased patient mortality, whereas hospitals with poor work environments were found to have the opposite outcome. In line with our study results, good nurse–physician relations and teamwork have been shown in a number of other studies to be positively related to patient safety outcomes 7 30…”
Section: Discussionsupporting
confidence: 92%
“…18 34 39–40 The finding that staffing adequacy was the only process measure of significance in the present study may be attributable to several factors. First, we used a selection of organisational process measures identified in a previous study; the measures used in other studies may not be compatible with our complex parameter.…”
Section: Discussionmentioning
confidence: 61%
“…[11][12][13][14][15] Several studies have presented associations between nurses' work environment and patient outcomes like adverse events, risk-adjusted mortality and patient satisfaction. [15][16][17][18][19][20][21] These are important studies identifying associations between patient outcome and features of the healthcare organisation. However, the way healthcare workers perceive and report patient safety serve as essential information to investigate how processes and structures support patient safe healthcare organisations.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%